Implementation of the Value Stream Mapping Method in the Process of Mixing Paving Block Materials to Reduce Waste in the Production Process at UD. Am Jaya - Muchammad, Alif; Misbah, Achmad (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
This study addresses critical inefficiencies in the paving block production process at UD. AM JAYA, where significant waste was identified in the material mixing stage, including excessive non-value-added time (31%), inventory bottlenecks, and suboptimal layout design. The research aims to systematically identify waste types using Lean Manufacturing principles, quantify production losses, and develop actionable improvements to enhance operational efficiency. Employing Value Stream Mapping (VSM) methodology, the study combines direct observation, time-motion studies (10 repeated measurements per process), and waste quantification through Current and Future State Mapping. Key findings reveal transportation waste (26% of total waste time) and waiting time (22%) as dominant issues, stemming from fragmented workstations and manual material handling. Implemented solutions - workstation consolidation, optimized material flow paths, and semi-automated equipment upgrades - yielded measurable outcomes: 18.24% reduction in cycle time (3,393.46 to 2,774.24 seconds), 24.24% shorter lead time (3.3 to 2.5 days), and elimination of 16.99 seconds of inter-station transportation.